2019
DOI: 10.1200/jco.2019.37.7_suppl.546
|View full text |Cite
|
Sign up to set email alerts
|

First-line pembrolizumab (pembro) monotherapy for advanced non-clear cell renal cell carcinoma (nccRCC): Results from KEYNOTE-427 cohort B.

Abstract: 546 Background: PD-1/L1 pathway inhibitors are effective in clear cell (cc)RCC, but efficacy of PD-1 inhibitors (or any therapy) in nccRCC has not been established. KEYNOTE-427 is a single-arm, open-label, phase 2 study of pembro monotherapy in patients (pts) with advanced ccRCC (cohort A) and nccRCC (cohort B). Cohort B results are presented. Methods: 165 pts with histologically confirmed nccRCC, no prior systemic therapy, measurable disease (RECIST v1.1), and KPS ≥70% enrolled. Pts received pembro 200 mg IV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 0 publications
2
29
0
Order By: Relevance
“…Among RCC types, most studies assessing efficacy of immune therapy have focused on ccRCC . Variable preliminary results on the performance of immune check‐point inhibitors in non‐ccRCC are forthcoming in two studies . McDermott et al .…”
Section: Discussionmentioning
confidence: 99%
“…Among RCC types, most studies assessing efficacy of immune therapy have focused on ccRCC . Variable preliminary results on the performance of immune check‐point inhibitors in non‐ccRCC are forthcoming in two studies . McDermott et al .…”
Section: Discussionmentioning
confidence: 99%
“…One evaluated atezolizumab plus bevacizumab and showed a response rate of 25% for nccRCC [29]. In the other, pembrolizumab was associated with response rates of 25.4% with papillary, 9.5% with chromophobe and 34.6% with unclassified nccRCC [30]. Certainly, in order to improve the outcomes in these subgroups of patients, the distinct behaviour of each histologic subtype needs to be recognised.…”
Section: Discussionmentioning
confidence: 99%
“…Small retrospective analyses do suggest a response to immune checkpoint inhibitor therapy in patients with nccRCC [17]. More recently, pembrolizumab has been studied in a singlearm, open-label, Phase 2 study (KEYNOTE-427), with a cohort of nccRCC patients who were treatment naïve [18]. This study of 165 patients demonstrated an objective response rate (ORR) of 24.8% overall; there was a suggestion towards differences in responses by subtype, with an ORR of 25.4% seen in patients with papillary subtype and of 9.5% seen in patients with chromophobe subtype.…”
Section: Discussionmentioning
confidence: 99%